518. Characterization of colistin-resistant (COL-R) Acinetobacter baumannii calcoaceticus complex (ABC) isolates from a recent, global Phase 3 trial (ATTACK). (15th December 2022) - Moussa, Samir; McLeod, Sarah; Miller, Alita
Abstract: Background: Due to the lack of effective therapies, last-resort agents such as colistin are more frequently being used to treat drug-resistant ABC infections. Consequently, COL-R ABC is becoming more common, with some countries such as Greece reporting rates of >50% 1 . The efficacy and safety of sulbactam-durlobactam (SUL-DUR) was recently compared to COL, both on a background of imipenem/cilastatin therapy, in patients with ABC infections, including those caused by multidrug-resistant strains. SUL-DUR was non-inferior to colistin with respect to 28-day all-cause mortality (19 vs. 32.3%). SUL-DUR therapy resulted in higher clinical cure rates and significantly improved safety compared to COL. Here, we describe COL-R ABC in ATTACK. Methods: Antibiotic susceptibility was determined by broth microdilution according to CLSI guidelines at IHMA, Inc. COL-R was defined as MIC ≥ 4 µg/ml. Next generation sequencing was performed using Nextera® libraries on an Illumina MiSeq system (San Diego, CA) at JMI Laboratories. Assembly and analysis were performed using CLC Genomics Workbench. Results: 17% (30 of 175) baseline ABC isolates from m-MITT (microbiologically modified Intent-to-Treat) patients were COL-R. All were extensively drug-resistant 2 and 26 were pan-drug resistant (PDR). Two additional ABC isolates became COL-R in patients with pneumonia who received COL therapy; neither patient survived to 28 days. Most came from 5 clinical sites: Hungary (N = 9), Russia (N = 7), Greece (N = 6), Israel (N = 4) and Turkey (N = 2). No COL-R ABC was found in China or the Americas. Sequencing analysis on selected isolates suggested sites in Hungary and Russia had clonal outbreaks, whereas others were non-clonal but closely related ( >99%). SUL-DUR was highly active in vitro against COL-R ABC isolates, with an MIC50/90 of 2/4 µg/ml. Of the 22 patients with COL-R ABC infections treated with SUL-DUR, 17 (77%) survived to 28 days with clinical and microbiological cure at test-of-cure (TOC). Conclusion: A notable number of ABC infections in ATTACK were COL-R, most of which were PDR but susceptible to SUL-DUR at ≤ 4 µg/ml. If approved, SUL-DUR could be an effective treatment for patients with these types of infections. 1. Nowak (2017) JAC, 72, 3277–3282 2. Magiorakis (2012) CMI, 18, 268-81 Disclosures: Samir Moussa, PhD, Entasis Therapeutics: Employee|Entasis Therapeutics: Stocks/Bonds Sarah McLeod, PhD, Entasis Therapeutics: Employee|Entasis Therapeutics: Stocks/Bonds Alita Miller, PhD, Entasis Therapeutics: Ownership Interest|Entasis Therapeutics: Stocks/Bonds.